Evaluation of left ventricular functions before and after iron therapy in patients with iron deficiency anemia - MUTLU, BÜLENT (My University, 2019)
The aim of present study is to evaluate left ventricular (LV) functions using speckle tracking echocardiography (STE) after iron therapy in patients with iron deficiency anemia (IDA). We consecutively enrolled 92 patients with IDA who needed iron therapy and 82 age- and gender-matched healthy volunteers in our study. Their clinical, laboratory, conventional two-dimensional echocardiography (2DE), and STE examinations were performed to all patients before and after iron therapy. Echocardiographic measurements were compared with healthy controls. The hemoglobin level increased after iron therapy (7.2±2.9 vs. 12.1±2.0, p<0.001). There was no statistically difference in conventional echocardiographic measurements of patients before and after iron therapy. The LV global longitudinal strain (GLS: 19.3±4.0 vs. 23.2±3.6, p<0.001), but it was still statistically lower than the LV GLS of the healthy controls (23.2±3.6 vs. 25.9±3.1, p<0.001). The LV global systolic strain rate increased after iron therapy (1.7±0.1 vs. 2.2±0.3, p<0.03). IDA might be associated with impairment in LV longitudinal myocardial function. STE might be useful both for early identification of LV subclinical impairment in patients with IDA and also improvement in myocardial deformation indices after iron therapy.